Reka bentuk model standard kompetensi pensyarah Kolej Vokasional Malaysia / Nor Hayati Ramlan - Nor Hayati , Ramlan (2018)
The purpose of this research is to develop The Standard Model of Vocational Colleges Lecturer Competence in Malaysia, specific for Civil Engineering Construction Technology course. The three rounds Delphi Technique used in this research involve need analysis phase, design phase and evaluation phase. Data from Needs Phase is collected through semi structured interview involving 15 participants.This phase purposely conducted to answer one research question. The data will be analysed by using qualitative analysis.In Design Phase, the data collected by using three rounds of Delphi Technique to answer one research question. 9 experts were interviewed in the first round. The findings were analysed using quantitative method reduction process, coding and categorizing data. The items identified used to form questionnaires in second and third round session. Data collected from second and third round were analysed using descriptive statistic to find mod, median and interquartile range. Data collection for Evaluation Phase from identified sample of lecturers that teach Construction Technology Course in 44 Vocational Colleges in all state in Peninsula Malaysia. The findings of this research answer two research questions and the data were analysed by using SPSS software version 20.0 and AMOS version 16.0 that used descriptive statistic method to find min score, standard deviation, percentage and Structural Equation Modelling (SEM). The data gathered for needs analysis phase showed that all respondents agree with the needs of designing the Standard Model of TVET Lecturer Competence in Civil Engineering Construction Technology in Vocational Colleges, Ministry of Education Malaysia. In the design phase, the data exhibited the consensus from 9 experts on the two domains of 4 dimensios with 42 sub dimension of Standard Model of TVET Lecturer Competence in Civil Engineering Construction Technology. There two domains of competencies are General Competency and Specific Competency. The dimension that supports the competencies domain are Profesionalisme, Generic Skills, Technical Skill of Civil Engineering Construction Technology and Technical Pedagogy Skill. In the assessment phase. the data show a high competency level from the respondents with the mean score recorded was greater than 3.67. The Standard Model of TVET Lecturer Competence in Civil Engineering Construction Technology is fit and found to be mean significant with the structural equation model (CSq=347.916, P=0.00, GFI = 0.856, AGFI = 0.836, CFI = 0.922, RMSEA = 0.07, CMIN/DF = 5.00 dan TLI = 0.862).This research suggests that The Standard Model of TVET Lecturer Competence in Civil Engineering Construction Technology that has been built can serve as a reference to the Ministry of Education especially Teacher Training Institute (TTI), public and private higher education institutions in preparing Technical Vocational Education and Training (TVET) lecturers specifically Construction Technology Course, Specialized Civil Engineering, highly skilled, competent and efficient to strengthen teacher’s profession especially in 21st century TVET Education.